Impact of meridional winds on the development of equatorial plasma bubbles: a review - Huba, J. D. (Frontiers in Astronomy and Space Sciences, 2024)
The impact of meridional winds on the onset and evolution of equatorial plasma bubbles (EPBs) is reviewed. The conventional wisdom had been that transequatorial meridional winds have a stabilizing effect on the development of EPBs during equatorial spread F (ESF). However, this result is based on a uniform transequatorial meridional wind. Subsequently, it was demonstrated that a non-uniform meridional wind could have a stabilizing or destabilizing effect on EPB formation depending on the direction of wind gradient. The destabilization of EPBs associated with equatorward flowing meridional winds has recently been investigated during a midnight temperature maximum event and a geomagnetic storm. Although the neutral wind is a direct destabilizing influence in these cases, the large decrease in the Pedersen conductance caused by meridional equatorward winds is the primary reason for the large increase in the growth rate of the generalized Rayleigh-Taylor instability. We review the theoretical and modeling studies of this topic as well as observational studies that have been made to assess the relationship between meridional winds and ESF.